A review on thermophysical properties, preparation, and heat transfer enhancement of conventional and hybrid nanofluids utilized in micro and mini channel heat sink - Sriharan, G.; Harikrishnan, S.; Öztop, Hakan Fehmi (Elsevier, 2023)
The rapid growing technological advancement in various miniatures thermal systems dissipate higher amount of heat. Hence, the miniature heat sinks such as mini channel and micro channel along with nanofluids are utilized to provide better cooling effect. The use of nanofluids not only provides better cooling the conduits of the MAMC prompts heat transfer characteristics. This study presents a review that highlights synthesis, characterization, and thermophysical properties of hybrid and conventional nanofluids. In addition, various shapes with different MAMC used in experimental and numerical models were also analyzed in detail. Despite several researches were conducted in the foresaid results, but there will be lots of conflict and contrariety, so it needs further investigation. This paper also reviewed the use of nanofluids in various conduits miniature devices. The purpose of present review would give a thorough and complete assessment of latest literature in this field, together with broad observations on its state of future development that trigger the new researchers in the field of miniature cooling system.
Keywords: Nanofluids; Thermal conductivity; Viscosity; Density; Specific heat transfer; Micro and mini channel heat sink; Hybrid nanofluids